2016
DOI: 10.4103/2230-8229.189133
|View full text |Cite
|
Sign up to set email alerts
|

Patients′ attitudes towards the participation of medical students in clinical examination and care in Western Saudi Arabia

Abstract: Background and Objectives:Patients are essential for the acquisition and development of medical students clinical skills for their tasks. The study aimed to identify factors that influence patients’ attitudes towards the involvement of medical students in clinical examination and care in Western Saudi Arabia.Methods:A cross-sectional study using self-administered questionnaire was conducted among Saudi and non-Saudi patients at two university hospitals in Jeddah, Western Saudi Arabia. Information sought includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
0
12
2
Order By: Relevance
“…Our cohort of patients were younger, with slightly more male participants when compared to other hospital surveys (84 years, 44% male patients), which could influence our results, as more negative patients attitude towards involving medical students in their care was observed in younger, female patients [14, 15]. …”
Section: Discussionmentioning
confidence: 84%
“…Our cohort of patients were younger, with slightly more male participants when compared to other hospital surveys (84 years, 44% male patients), which could influence our results, as more negative patients attitude towards involving medical students in their care was observed in younger, female patients [14, 15]. …”
Section: Discussionmentioning
confidence: 84%
“…Only 23% of patients were comfortable with a male medical student examining them compared to 45% with a female medical student (1). The fact that female patients were less comfortable with being examined by male medical students has also been noted in several other studies (2,3).…”
Section: The Several Layers Of Being Comfortablementioning
confidence: 75%
“…However, patients in inpatient wards may be uncomfortable or completely unwilling to allow medical students to examine them, or perform any procedure or invasive examinations on them. This could be because patients do not have complete confidence in the students' skills, or because of a general discomfort with medical students performing these procedures (3). A US study by Graber et al, found that the majority of patients in the emergency room would not let medical students perform any procedure, including venepuncture (4).…”
Section: The Several Layers Of Being Comfortablementioning
confidence: 99%
“…Additionally, there was no statistically significant correlation between patients' attitudes and marital status, education level, hospital type, or prior interactions with medical students. 19 Exploring patients' perceptions and attitudes towards their interaction with medical students is necessary for responding to their expectations and for enhancing the quality of the health care provided to them. This will be the first study to assess this subject in Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…Those findings correspond with our study results which showed that 91.9% of the participants approved of medical students' existence during their consultation. 19,25 However, this depends on the type and characteristics of the encounter. For example, more than 80% approved medical students to take medical history from them, and 74.5% allowed students to assist in the plan of care.…”
mentioning
confidence: 99%